(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Abdominal pregnancy is a rare form of ectopic pregnancy and a serious form of extrauterine pregnancy. Abdominal pregnancy account for almost 1% of ectopic pregnancies. Rarely,it may reach at advanced gestation and a viable fetal outcome is a rare event. Sometimes, the diagnosis is suspected only when repeated attempts of induction of abortion or labor are unsuccessful. Really it is difficult to diagnose and manage. Here we are reporting a case of secondary abdominal pregnancy in a 27 years old primi gravida at 39+ weeks of gestation. It was observed from her ultrasonography that a single live pregnancy with breech presentation with almost absent liquor with IUGR baby then decision was made for lower uterine cesarean section under sub-arachnoid block. But it was turned into laparotomy and diagnosed as a secondary abdominal pregnancy. A healthy female baby was delivered. The placenta was attached with the omentum and large bowel loop. After tying and cutting the cord flushed with it’s placental attachment, placenta was kept in situ. Abdomen was closed in layers. The diagnosis of abdominal pregnancy was made preoperatively with successful management and delivery of a healthy female baby. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):104-106